2019
DOI: 10.1093/mnras/stz1394
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution of rotating and magnetized white dwarf stars

Abstract: We investigate the evolution of isolated, zero and finite temperature, massive, uniformly rotating and highly magnetized white dwarf stars under angular momentum loss driven by magnetic dipole braking. We consider the structure and thermal evolution of white dwarf isothermal cores taking also into account the nuclear burning and neutrino emission processes. We estimate the white dwarf lifetime before it reaches the condition either for a type Ia supernova explosion or for the gravitational collapse to a neutro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Simulations of mergers of WDs leading to magnetic super-Chandrasekhar WDs have been performed [65] leading to a maximum mass of 1.45 M . For the case of isolated sources, it would be 1.46 M [10]. This is in accordance with new observations such as the one in Ref.…”
Section: Massive White Dwarfs On the Grounds Of Modified Gravitysupporting
confidence: 92%
See 1 more Smart Citation
“…Simulations of mergers of WDs leading to magnetic super-Chandrasekhar WDs have been performed [65] leading to a maximum mass of 1.45 M . For the case of isolated sources, it would be 1.46 M [10]. This is in accordance with new observations such as the one in Ref.…”
Section: Massive White Dwarfs On the Grounds Of Modified Gravitysupporting
confidence: 92%
“…In this context, plenty of works have been done to model these very massive white dwarfs (MWD). The properties of MWDs have been studied in different contexts: rotation [7][8][9][10]; high electric and magnetic fields [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]; temperature [27,28] and modified gravity [29][30][31][32][33][34][35][36][37][38][39][40]. It has been shown that general relativistic effects are essential for massive white dwarfs and cannot a e-mail: r.vieira@uniandes.edu.co b e-mail: araujogc@ita.br c e-mail: nkelkar@uniandes.edu.co d e-mail: mnowakos@uniandes.edu.co (corresponding author) be disregarded [41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…There are also a plethora of observational data for carbon and other WDs [23,24]. The time and thermal evolution of carbon WDs has been theoretically investigated involving the nuclear burning and neutrino emission processes [25]. The observational support of the existence of iron-rich cores of WDs was given in Ref.…”
Section: Problem Setup and Methodologymentioning
confidence: 99%
“…It is well know that unlike magnetic field or anisotropic pressure, rotation is the main contributor to the deformation of compact objects such as WDs and NSs [69][70][71]. Here by exploiting the HT formalism [37,38,72] the rotating equilibrium configurations of WDs [73,74] and NSs [69,75,76] are constructed and the mass quadrupole moment as a function of central density for maximally rotating stars (see Fig.…”
Section: Rotating White Dwarfs and Neutron Starsmentioning
confidence: 99%